Astigmat Kornea Pada Penderita Katarak - Inayah Tria Putri; Nofri Suriadi (Jurnal Ilmu Kedokteran, 2021)
Corneal astigmatism in cataract patients can cause poor visions after cataract surgery. Patients could have optimum visions without glasses by toric IOL implants during cataract surgery. This study aimed to find the distribution of corneal astigmatism in cataract patients based on age, gender, race, type of astigmatism, and astigmatism level. This study was a descriptive prospective study with cross sectional design with 550 eyes from 556 patients. The samples were collected from eligible patient’s keratometric data in RSUD Arifin Achmad Provinsi Riau, RS Mata Pekanbaru Eye Center, and RS Bina Kasih Pekanbaru. The results of the study showed 60.9% of cataract patients had corneal astigmatism and 61.7% of patients with astigmatic (37.2% of cataract patients) were moderate, severe, and extreme astigmatic that required correction with toric IOL. Most of the ages were 60-69 years old (42.2%). The characteristic of the patients was dominated by men (51.6%). The most common race is Malay Mongoloid (97.6%). The most type of astigmatism is astigmatism with the rule (ATR) (42.9%).